Crop residue degradation by fungi isolated from conservation agriculture fields under riceâwheat system of North-West India - Madhu Choudhary; Parbodh C. Sharma; Hanuman S. Jat; Vibha Nehra; Andrew J. McDonald; Neelam Garg (International Journal of Recycling of Organic Waste in Agriculture)
Purpose In North West-Indo Gangetic Plains (NW-IGP) of India in situ burning of crop residues is practiced by majority of farmersâ which deteriorates soil and environmental quality. Fungi have the potential for lignocellulose degradation and can be used for the in situ decomposition of crop residues. Lignocellulose degrading fungal spp. were isolated and evaluated for the activity of lignocellulolytic enzymes. Method The lignocellulose degrading fungi were isolated by appearance of zone on carboxy methyl cellulose (CMC) agar media and tannic acid (TA) media. Carboxy methyl cellulase, filter paperase, cellobiase, xylanase and laccase activity were estimated in submerged, as well as solid state fermentation using a mixture of rice and wheat straw in the ratio of 4:1. riceâwheat straw as substrate. The residue left after solid state fermentation was evaluated for carbon/nitrogen ratio, dry mass loss, and loss of cellulose, hemicellulose and lignin. Selected potential isolates were further tested in pot experiment for their effect on wheat plants. The interaction among isolates was also studied. Result After primary screening, 19 out of a total of 72 fungal isolates were selected based on their enzymatic activity profile and potential to degrade lignocellulosic residues in submerged fermentation. Out of these 19 isolates, 11 were further selected based on their enzymatic secretions in solid state fermentation. All the 11 strains were identified morphologically. Four fungal isolates (RPW 1/3, RPW 1/6, RPWM 2/2 and RZWM 3/2) showed higher enzymatic activities and more loss of dry mass and cell wall constituents over the other isolates. These isolates were identified by ITS region sequencing as Aspergillus flavus, Aspergillus terreus, Penicillium pinophilum and Alternaria alternata. Conclusion This study revealed that fungal isolates may be used for managing crop residues in conservation agriculture based riceâwheat system of NW-IGP to eliminate ill effects of residue burning.